Anti-cytokine autoantibodies in human susceptibility to infectious diseases: insights from Inborn errors of immunity - Kosuke Noma; Takaki Asano; Maki Taniguchi; Kosuke Ashihara; Satoshi Okada (Immunological Medicine)
The study of Inborn Errors of Immunity (IEIs) is critical for understanding the complex mechanisms of the human immune response to infectious diseases. Specific IEIs, characterized by selective susceptibility to certain pathogens, have enhanced our understanding of the key molecular pathways and cellular subsets involved in host defense against pathogens. These insights revealed that patients with anti-cytokine autoantibodies exhibit phenotypes similar to those with pathogenic mutations in genes encoding signaling molecules. This new disease concept is currently categorized as ‘Phenocopies of IEI’. This category includes anti-cytokine autoantibodies targeting IL-17/IL-22, IFN-γ, IL-6, GM-CSF, and type I IFNs. Abundant anti-cytokine autoantibodies deplete corresponding cytokines, impair signaling pathways, and increase susceptibility to specific pathogens. We herein demonstrate the clinical and etiological significance of anti-cytokine autoantibodies in human immunity to pathogens. Insights from studies of rare IEIs underscore the pathological importance of cytokine-targeting autoantibodies. Simultaneously, the diverse clinical phenotype of patients with these autoantibodies suggests that the influences of cytokine dysfunction are broader than previously recognized. Furthermore, comprehensive studies prompted by the COVID-19 pandemic highlighted the substantial clinical impact of autoantibodies and their potential role in shaping the outcomes of infectious disease.